CRISPR/Cas in iPSCs from sphingolipidoses patients - Moreira, Luciana (2020)
This work was also financially supportedby National Funds through FCT—Fundacao da Ciencia e Tecno-logia (MCTES—Portugal) under Project ‘‘PTDC/BIM-MEC/4762/2014"